Study on the correlation between microstructural evolution and hydrogen storage properties in hyper-eutectic Mg-xNi (x = 15, 20, 25) alloys - So Jin Jung; Seok Su Sohn; Da Hye Lee; Won-Seok Ko; Tae Jun Ha; Ryun-Ho Kwak; Byeong-Chan Suh; Young Min Kim; Hyung-Ki Park (Journal of Materials Research and Technology)
This study investigated the effect of Ni content on the microstructure and hydrogen storage properties of hyper-eutectic Mg–Ni hydrogen storage alloys. Mg-xNi (x = 15, 20, 25 (at%)) alloys were prepared using vacuum induction melting. These alloys consisted of a primary Mg2Ni phase and an Mg–Mg2Ni lamellar structure, with the proportion of the primary Mg2Ni phase increasing as the Ni content rose. The hydrogen absorption and desorption behaviors of the alloys were analyzed at 325 °C. The maximum hydrogen storage capacity of the Mg–15Ni alloy was 5.29 wt%. As the Ni content increased, the phase percentage of the Mg2Ni phase increased, leading to a reduction in the maximum hydrogen storage capacities of the Mg–20Ni and Mg–25Ni alloys to 5.01 and 4.67 wt%, respectively. Although the maximum hydrogen storage capacity varied with Ni content, both the first plateau pressure (Mg → MgH2) and the second plateau pressure (Mg2Ni → Mg2NiH4) during hydrogen absorption remained unchanged and consistent across all three alloys. To understand why the plateau pressure remained constant despite variations in alloy composition, the equilibrium compositions of the Mg and Mg2Ni phases in the alloys were calculated through thermodynamic calculations. In addition, the compositions of the Mg and Mg2Ni phases within the lamellar structure were analyzed using transmission electron microscope. These analyses confirmed that, despite variations in Ni content across the alloys, the chemical composition of the individual Mg and Mg2Ni phases remained unchanged. The Mg phase exhibited a 100% Mg composition, while the Mg2Ni phase showed an atomic ratio of Mg to Ni of 2:1, closely matching the theoretical stoichiometric ratio. In hydrogen storage alloys, plateau pressures are influenced by the composition of each phase rather than the overall composition of the alloy. Consequently, even with changes in Ni content in the hyper-eutectic Mg–Ni alloys, the plateau pressures remained unchanged. When Ni is added to Mg hydrogen storage alloys, the hydrogen reaction kinetics are improved. However, this study confirmed that, despite the increase in Ni content, the plateau pressures remained unchanged, while the maximum hydrogen storage capacities decreased. Therefore, it is essential to derive an optimal Mg–Ni alloy composition that balances both reaction kinetics and hydrogen storage capacity.